Effects of age-related hearing loss and background noise on neuromagnetic activity from auditory cortex - Alain, Claude (Frontiers in Systems Neuroscience, 2014)
Aging is often accompanied by hearing loss, which impacts how sounds are processed and represented along the ascending auditory pathways and within the auditory cortices. Here, we assess the impact of mild binaural hearing loss on the older adults’ ability to both process complex sounds embedded in noise and segregate a mistuned harmonic in an otherwise periodic stimulus. We measured auditory evoked fields (AEFs) using magnetoencephalography while participants were presented with complex tones that had either all harmonics in tune or had the third harmonic mistuned by 4 or 16% of its original value. The tones (75 dB sound pressure level, SPL) were presented without, with low (45 dBA, SPL) or with moderate (65 dBA SPL) Gaussian noise. For each participant, we modeled the AEFs with a pair of dipoles in the superior temporal plane. We then examined the effects of hearing loss and noise on the amplitude and latency of the resulting source waveforms. In the present study, results revealed that similar noise-induced increases in N1m were present in older adults with and without hearing loss. Our results also showed that the P1m amplitude was larger in the hearing impaired than normal-hearing adults. In addition, the object-related negativity (ORN) elicited by the mistuned harmonic was larger in hearing impaired listeners. The enhanced P1m and ORN amplitude in the hearing impaired older adults suggests that hearing loss increased neural excitability in auditory cortices, which could be related to deficits in inhibitory control.